Debt Financing Options and Financial Performance - Franky Ardiyanto (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
The Sector that has greatest impact on debt financing is Sector food and beverage company use imported raw material. In this case, company is required to be able to regulate the level of debt to the company. This study analysis examine the influence between debt financing option and Financial Performance. Analysis carried out using multiple linear analysis by taking sample data use sample proportion or with the specified criteria which has been specified and obtained as many as 11 companies with total observation of 55 in food and beverage companies listed on the Indonesian stock exchange 2014-2018. Based on hypothesis testing Short Term Debt and Long Term Debt does affect between Return On Asset. Than, Short Term Debt does affect between Return On Equity. However, Long Term Debt does not affect between Return On Equity.